PEMBAGIAN WARIS ANAK ANGKAT DALAM PERSPEKTIF TAFSIR MAQASIDI DAN HUKUM NASIONAL - Salmah Husein (SINERGI : Jurnal Riset Ilmiah, 2026)
ABSTRACT Adoption in Indonesia is legally recognized, but adopted children do not automatically become heirs because they do not fulfill the principles of lineage or marriage. The Civil Code (Article 832) and KHI (Article 174 paragraph 1) limit ab-intestato inheritance to blood relatives and husband and wife; while the Qur'an surah al-Ahzab verse 4 and the hadiths of the Prophet emphasize that lineages can only be formed through biological relationships or legal vows. This article aims to examine the economic protection of adopted children according to national law and maqāṣidī interpretations. Using a qualitative-comparative method, data was collected from statutory regulations, jurisprudence of MA No. 1/Yur/Ag/2018, as well as contemporary maqaṣid tafsir literature. The research results show: (1) The mandatory will mechanism (KHI Article 209 paragraph 2) allows adopted children to receive a maximum of 1/3 of the inheritance if the heir does not leave a will; (2) Islam allows gifts during life and wills of a maximum of 1/3 without damaging the fara'iḍ quota; (3) The provision of the grant/will is proven to be consistent with the maqaṣid sharia of maintaining economic justice (ḥifẓ al-mal), strengthening family ties (hifz al-nasl), and guaranteeing order and peace (hifz al-nafs and al-'aql) without falsifying the nasab. In conclusion, both national law and maqāṣidī interpretations offer inclusive and humanist solutions that uphold substantive justice for adopted children without sacrificing the basic principles of lineage-based inheritance. ABSTRAK Pengangkatan anak (adopsi) di Indonesia memperoleh pengakuan hukum, namun anak angkat tidak serta-merta menjadi ahli waris karena tidak memenuhi prinsip nasab maupun perkawinan. KUH Perdata (Pasal 832) dan KHI (Pasal 174 ayat 1) membatasi waris ab-intestato kepada keluarga sedarah dan suami-istri; sedangkan al-Qur’an surah al-Ahzab ayat 4 dan hadis-hadis nabi menegaskan bahwa nasab hanya dapat dibentuk melalui hubungan biologis atau ikrar sah. Tulisan ini bertujuan menelaah perlindungan ekonomi anak angkat menurut hukum nasional dan tafsir maqāṣidī. Dengan metode kualitatif-komparatif, data dihimpun dari peraturan perundang-undangan, yurisprudensi MA No. 1/Yur/Ag/2018, serta literatur tafsir maqaṣid kontemporer. Hasil penelitian menunjukkan: (1) Mekanisme wasiat wajibah (KHI Pasal 209 ayat 2) memungkinkan anak angkat menerima maksimal 1/3 harta peninggalan apabila pewaris tidak meninggalkan wasiat; (2) Islam memperbolehkan hibah semasa hidup dan wasiat maksimal 1/3 tanpa merusak kuota fara’iḍ; (3) Pemberian hibah/wasiat tersebut teruji konsisten dengan maqaṣid syariah menjaga keadilan ekonomi (ḥifẓ al-mal), mempererat ukhuwah keluarga (hifz al-nasl), serta menjamin ketertiban dan kedamaian (hifz al-nafs dan al-‘aql) tanpa memalsukan nasab. Kesimpulannya, baik hukum nasional maupun tafsir maqāṣidī menawarkan solusi inklusif dan humanis yang menegakkan keadilan substantif bagi anak angkat tanpa mengorbankan prinsip dasar waris berbasis nasab.